2017
DOI: 10.1128/aem.01270-17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chlorine Treatment Levels for Inactivation of Human Norovirus and MS2 Bacteriophage during Sewage Treatment

Abstract: This study examined the inactivation of human norovirus (HuNoV) GI.1 and GII.4 by chlorine under conditions mimicking sewage treatment. Using a porcine gastric mucin-magnetic bead (PGM-MB) assay, no statistically significant loss in HuNoV binding (inactivation) was observed for secondary effluent treatments of ≤25 ppm total chlorine; for both strains, 50 and 100 ppm treatments resulted in ≤0.8-log unit and ≥3.9-log unit reductions, respectively. Treatments of 10, 25, 50, and 100 ppm chlorine inactivated 0.31, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…For chlorine, our data showed that complete inactivation of 3 different GII.4 strains could be achieved with concentrations as low as 50 ppm. These results are consistent with a recent report indicating that treatment with chlorine concentrations <50 ppm were not sufficient to inactivate human norovirus in secondary effluents from water treatment plants ( 31 ). In conclusion, our inactivation data demonstrate that chlorine, but not alcohol, completely inactivates human norovirus and that evaluation of inactivation strategies based only on detection of viral RNA does not always reflect the effectiveness of the treatment.…”
Section: Discussionsupporting
confidence: 93%
“…For chlorine, our data showed that complete inactivation of 3 different GII.4 strains could be achieved with concentrations as low as 50 ppm. These results are consistent with a recent report indicating that treatment with chlorine concentrations <50 ppm were not sufficient to inactivate human norovirus in secondary effluents from water treatment plants ( 31 ). In conclusion, our inactivation data demonstrate that chlorine, but not alcohol, completely inactivates human norovirus and that evaluation of inactivation strategies based only on detection of viral RNA does not always reflect the effectiveness of the treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Similar trends were found with HuNoV GI.1, and GII.4 treated with high CTs of free chlorine lost its ability to bind to PGM-MBs. 48,49 and chlorine treatment at C 0 ≤ 25 ppm did not cause binding loss of HuNoV to PGM-MBs. 48 In addition to protein damage, free chlorine penetrates inside the TV virions to damage its genome at least partially.…”
Section: ■ Discussion and Implicationmentioning
confidence: 85%
“…Drinking water from municipal supplies fed by lake or groundwater has already been identified in the past as the source of waterborne NoV outbreaks in Italy [2729] and NoV is now considered one of the pathogens causing the largest number of affected consumers in drinking waterborne outbreaks [12]. NoV can persist in water longer than 15 days [30] and it is resistant to chlorine disinfection when free chlorine levels or pre-treatment processes are inadequate [31, 32]. Moreover, microfiltration filters labelled as certified by NSF Standards 53 or 58 (with a pore size ranging from 0.05 to 5 µm) are not effective in removing viruses and can even decrease chlorine concentration in filtered water [33].…”
Section: Discussionmentioning
confidence: 99%